Recurrences For Harmonic Sums
Let h(n) denote the nth partial sum of the harmonic series, and define
H[k] = h(2^k). It's not hard to show that H[n] approaches a linear
recurring sequence satisfying
H[k] - 2 H[k-1] + H[k-2] = 0
as k increases. The error of this recurrence decreases by a factor of
two at each step. Correcting for this error, we arrive at the third-
order recurrence
2 H[k] - 5 H[k-1] + 4 H[k-2] - H[k-3] = 0
Eliminating the main error term from this relation leads to a fourth-
order recurrence, and so on. The coefficients of these recurrences
up through order six are tabulated below (without signs):
(2) 1 2 1
(4) 2 5 4 1
(16) 8 22 21 8 1
(64) 128 360 358 149 24 1
(256) 8192 23168 23272 9894 1685 88 1
The numbers in parentheses on the left indicate the factor by which
the error of the respective recurrence decreases at each step. If
c[i,j] denotes the coefficient in the ith row and the jth column,
and r_i denotes the "error factor" of the ith row, then the rule
of formation for these coefficients can be expressed as
c[i,j] = (r_(i-1)) c[i-1,j] + c[i-1,j-1]
Note that the sum of the elements of each row, with alternating signs,
is zero. Also, the "error factor" increases by a multiple of 4 at
each level except the first, so we have r_1 = 2 and r_i = 4^(i-1)
for i>1.
This same approach works for other geometric arguments, e.g., if we
define G[k] = h(3^k), we can derive a sequence of recurrences with the
coefficients listed below (without signs):
(3) 1 2 1
(9) 3 7 5 1
(81) 27 66 52 14 1
The rule of formation is the same, except that in this case we have
r_1 = 3 and r_i = 9^(i-1) for i>1.
To generalize this a bit, for any fixed integer m>1 define
H[k] = h(m^k)
Since h(n) increases logrithmically, it's natural to expect that the
above recurrence is a good starting point for any m, because
ln(m^k) + A ln(m^(k-1)) + B ln(m^(k-2))
= k ln(m) + A (k-1) ln(m) + B (k-2) ln(m)
Setting this equal to zero and dividing by ln(m) gives
k + A (k-1) + B (k-2) = k(1+A+B) - (A+2B) = 0
which implies the two conditions
1 + A + B = 0 A + 2B = 0
so we must have A=-2 and B=1. However, the third order recurrence
for h(m^k) gives only two constraints on three coefficients, i.e.,
1 + A + B + C = 0 A + 2B + 3C = 0
and similarly for higher order recurrences. Thus, all recurrences for
ln(m^k) of order greater than 2 are underspecified. Anyway, taking the
order 2 recurrence we see that the characteristic polynomial splits
into linear factors
x^2 - 2x + 1 = (x-1)^2
It turns out that the characteristic polynomials of all the asymptotic
recurrences for H[k] described previously also split into linear factors.
Specifically, for m=2 we have
2x^3 - 5x^2 + 4x - 1 = (2x-1)(x-1)^2
8x^4 - 22x^3 + 21x^2 - 8x + 1 = (4x-1)(2x-1)(x-1)^2
128x^5 - 360x^4 + 358x^3 - 149x^2 + 24x - 1 = (16x-1)(4x-1)(2x-1)(x-1)^2
and so on. Similarly for m=3 we have
3x^3 - 7x^2 + 5x - 1 = (3x-1)(x-1)^2
27x^4 - 66x^3 + 52x^2 - 14x + 1 = (9x-1)(3x-1)(x-1)^2
and so on. In general, the characteristic polynomial of the asymptotic
Jth-order recurrence (J>3) for H[k] with any fixed m is
J-3
P(x) = (mx-1) (x-1)^2 PROD (m^(2t) x - 1)
t=1
so the characteristic roots (eigen values) are
1, 1, 1/m, 1/m^2, 1/m^4, 1/m^6,..., 1/m^(2(J-3))
This allows us to give an explicit formula for the terms of the
Jth-order linear recurring sequence of values that approximate H[k].
Let Q be a JxJ matrix with the components
Q[i,1] = 1 for i=1 to J
Q[i,2] = i for i=1 to J
Q[i,3] = 1/m^i for i=1 to J
Q[i,j] = 1/m^2i(j-3) for i=1 to J and j=4 to J
and let R be a column vector with the components
R[i] = H[i-1] for i=1 to J
Then the asymptotic recurrence for H[k] has the following closed-form
solution using the exact values H[0] through H[J-1] as initial values:
H[k-1] = [ 1 k 1/m^k 1/m^2k 1/m^4k ... 1/m^(2k(J-3)) ] Q^-1 R
Clearly, as k increases, all but the first two terms of this expression
go to zero, so for large values of k we have approximately
H[k-1] = C[1] + C[2]*k
where C[1] and C[2] are the first two components of the column vector
C = Q^-1 R. The difference between H[k-1] and h(2^(k-1)) is therefore
approximated by
C[1] + C[2] k - (k-1) ln(2)
= C[1] + ln(2) + k ( C[2] - ln(2) )
For high order recurrence this value becomes virtually independent of
k, which suggests that C[2] approaches ln(2). Making this substitution,
we would expect to find that
gamma ~= C[1] + C[2]
To illustrate, with m=2 the closed-form solution for the 6th-order
recurrence gives
C[1] + C[2] = 0.5772175....
which is approximately equal to gamma = 0.5772156...
Return to MathPages Main Menu